Produccion de semilla de yuca - López, J. (1989)
Parameters for the production of high-quality cassava seed are presented. The 3 aspects considered regarding the seed should be genetic (branching habit and overall vigor), physiological (seed age, nutrition, and viability, age of mother plant), and sanitary. Both systemic (fungi, bacteria, mycoplasmas, viruses) and localized pathogens are discussed in addition to cutting-transmitted pests found either (1) adhered to the stem such as mites, scale insects, mealybugs, and thrips or (2) located within the stem such as fruit flies, stemborers, and termites. Two selection systems are proposed to improve the quality of planting material: selection by meristem culture and selection for high yielding plants. Different aspects to be considered in seed lot selection and preparation are indicated. (CIAT)